The Incidence of Maxillofacial Trauma Post ORIF on The Incidence of Chronic Sinusitis - Salsabila, Tasya Viona; Hafizh, Imam Nur; Adji, Iwan Setiawan (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to investigate the incidence of chronic sinusitis following Open Reduction and Internal Fixation (ORIF) for maxillofacial fractures. The research focuses on the impact of ORIF on sinus anatomy, drainage, and ventilation, leading to potential sinus complications. Methodology: The methodology used in this report is a clinical case study. Data were collected through anamnesis, physical examination, and supporting examinations. The patient's management was analyzed based on existing medical theories and appropriate treatment was provided according to the patient's condition. Results: Cases analyzed show common risk factors such as hematosinus, sinus flow obstruction, and postoperative swelling. The study emphasizes the need for post-surgical monitoring (3-6 months) to assess the development of sinusitis and related complications. Applications/Originality/Value: This report provides insights into the importance of early diagnosis and proper management maxillofacial trauma.The findings can be useful for healthcare professionals to understand clinical signs and effective treatment approaches for similar cases. Postoperative monitoring should include imaging and clinical evaluations to detect early signs of sinusitis.